Thiabowls: synthesis, molecular structure and the solid state architecture of tetrathia-[4]-peristylane - Mehta, Goverdhan; Gagliardini, Vanessa; Schaefer, Carsten; Gleiter, Rolf (Tetrahedron letters, 2003)
Synthesis of tetrathia-[4]-peristylane, the first thiabowl, from the dimer of cyclooctatetraene has been accomplished. The X-ray crystal structure of the tetrathiabowl indicates significant departure from the expected C4v symmetry and in the solid state it exhibits a multi-columnar arrangement and a novel ‘self-inclusion’ phenomenon, directed by a network of S⋯S and CH⋯S interactions.